Watkins wheat landraces decode nitrogen-driven biomass trade-offs: GWAS exposes root-shoot dialectics and elite landraces for resilient agriculture - Waheed, Abdul; Iqbal, Muhammad Shahid; Sarfraz, Zareen; Hou, Junliang; Wei, Yanping; Song, Bo; Cheng, Shifeng (Frontiers in Plant Science, 2025)
IntroductionNitrogen limitation is a critical abiotic stressor that disrupts the balance between plants and their environment, imposing trade-offs in biomass allocation that threaten crop productivity and food security. While modern breeding programs often focus on improving shoot performance, the genetic mechanisms that coordinate root-shoot responses under nitrogen stress remain poorly understood. This study aimed to dissect the molecular and physiological foundations of nitrogen-driven resilience in wheat, leveraging the genetically diverse Watkins wheat landraces as a source of adaptive alleles.MethodsA total of 308 Watkins wheat landraces were phenotyped under low nitrogen (LN) and normal nitrogen (NN) conditions to assess root-shoot allocation strategies. Genome-wide association studies (GWAS) were conducted to identify candidate genes governing nitrogen-responsive traits. Functional annotation and transcriptomic validation were used to elucidate gene networks, and haplotype mapping was employed to link allelic variation to geographic adaptation. Multivariate analysis was performed to classify biomass allocation strategies among the landraces.ResultsPhenotypic analysis revealed stark differences in root-shoot allocation strategies under LN and NN conditions. GWAS identified 130 candidate genes, including root-specific RALF33 and shoot-prioritizing TaNAR1, involved in nitrogen-responsive traits. Functional studies highlighted antagonistic gene networks, such as TAF6 and TaAPY6, balancing root meristem activity and stress adaptation. Adaptive alleles of RALF33 in European landraces optimized root proliferation under LN, while Eurasian landraces exhibited shoot-root coordination under NN through TaNAR1 variants. Multivariate analysis classified landraces into four distinct biomass allocation strategies, identifying elite genotypes resilient to nitrogen limitation.DiscussionBy integrating genomics, phenomics, and haplotype mapping, this study connects molecular mechanisms underlying nutrient stress with ecophysiological adaptation. Key genes, such as RALF33 and TaAPY6, emerged as actionable targets for marker-assisted breeding to develop nitrogen-efficient wheat varieties. These findings highlight the potential of evolutionary-informed genetics in the Watkins landraces to enhance stress resilience, providing a roadmap for sustainable crop design in the context of global nutrient scarcity.